Genomic profiling and sites of metastasis in non-small cell lung cancer - Chan, Kok Hoe; Sridhar, Arthi; Lin, Ji Zheng; Jafri, Syed Hassan Raza (Frontiers in Oncology, 2023)
Background: We investigated the biological predisposition to site of metastasis in patients with NSCLC based on their molecular profiling and program death ligand PD-L1 status. We sought to identify any association between metastatic site and molecular profile in NSCLC patients. Methods: This was a retrospective analysis of patients with stage IV NSCLC who were newly diagnosed from January 2014-June 2022. Clinical characteristics, pathology, molecular reports, and imaging were retrieved and analyzed. Results: A total of 143 patients were included in the study. Median age was 65 years, with an equal number of men (n=71) and women (n=72). The most common histology was adenocarcinoma (81.8%). At least one genetic mutation was discovered in 100 patients. Mutations with a targetable drug were found in 86 patients. The most common mutations were TP53 (25.2%), EGFR (24.5%), KRAS/NRAS (20.3%), and CDKN2A/2B (7.7%). Patients with any mutation were significantly more likely to have metastatic disease to the brain (57% vs. 37%, p=0.03), but there was no difference in metastatic disease to bone (34% vs. 26%, p=0.32). Patients without a discoverable mutation were significantly more likely to have metastatic disease to other sites (e.g., adrenal gland 91% vs. liver 66%, p=0.002). There was no difference in progression-free survival (PFS) or overall survival (OS) between those with versus without mutations. Median PFS and OS were significantly longer in patients with an EGFR mutation than those with KRAS/NRAS or TP53 mutations. Patients with PD-L1 >1% or TP53 were significantly more likely to have metastatic disease to organs other than bone or brain (p=0.047 and p=0.023, respectively). We identified four prognostic groups in metastatic NSCLC. Patients with PD-L1 <1% and no actionable mutations have the poorest prognosis, with median survival of around 20 months. Conclusion: Patients with mutations discoverable on NGS are more likely to have metastatic disease to the brain. KRAS/NRAS in particular has a predilection to metastasize to the brain and bone. PD-L1 expression and a TP53 mutation, on the other hand, tend to lead to metastasis of NSCLC to organs other than brain or bone. These results need to be corroborated in larger prospective studies.